12x+10+3x=(2+13)x-6+16

Simple and best practice solution for 12x+10+3x=(2+13)x-6+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x+10+3x=(2+13)x-6+16 equation:


Simplifying
12x + 10 + 3x = (2 + 13) * x + -6 + 16

Reorder the terms:
10 + 12x + 3x = (2 + 13) * x + -6 + 16

Combine like terms: 12x + 3x = 15x
10 + 15x = (2 + 13) * x + -6 + 16

Combine like terms: 2 + 13 = 15
10 + 15x = (15) * x + -6 + 16

Reorder the terms:
10 + 15x = -6 + 16 + 15x

Combine like terms: -6 + 16 = 10
10 + 15x = 10 + 15x

Add '-10' to each side of the equation.
10 + -10 + 15x = 10 + -10 + 15x

Combine like terms: 10 + -10 = 0
0 + 15x = 10 + -10 + 15x
15x = 10 + -10 + 15x

Combine like terms: 10 + -10 = 0
15x = 0 + 15x
15x = 15x

Add '-15x' to each side of the equation.
15x + -15x = 15x + -15x

Combine like terms: 15x + -15x = 0
0 = 15x + -15x

Combine like terms: 15x + -15x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 7a^2+49a-210=0 | | B*2-a*3+1=0 | | 11x+1y=3 | | 3m+9=5m-5 | | x+2*64=6*64 | | 10(x+1)=5x+25 | | 2(w+l)=2w+2l | | 3(x+20)=15 | | x/6-x/7=3/7 | | (a-16)/5=29 | | a-16/5=29 | | a-16/5=-8 | | 12x-18=10x | | 7(v-4)=14 | | (a-16)/5=-8 | | -6u+3=-3(u-3) | | 6sen(A)-3=0 | | -3m=-4+8 | | a^2+11a+10=0 | | (6d+5)(d-8)= | | X/5=12/35 | | 28x^2-94x+60=0 | | 28x^2-94x+30=0 | | (3c^2+2c-1)(2c^2+c+9)= | | xy-2a-2x+ay= | | 3x^2+9x-1= | | (3c+2c-1)(2c^2+c+9)= | | 3a^2+6a+2=0 | | 3u^3+15u^2-87u-315=0 | | -10.8/-2= | | 4+3(3a+3)=5 | | 0.01x-1.5=0.009 |

Equations solver categories